Kings of the earth : a novel - Clinch, Jon. (New York : Random House, 2010)
On a primitive farm on the margins of an upstate New York town, three Proctor brothers live together in a kind of crumbling stasis--until one of them dies in his sleep and the other two are suspected of murder. A deeply intimate saga of the human condition at its limits.
Keywords: Rural families -- Fiction; Brothers -- Fiction; Murder -- Fiction